Description of the tadpoles of Phyllodytes brevirostris (Anura: Hylidae) - Vieira, Washington L. S.; Santana, Gindomar G.; Da Nóbrega Carneiro Dos Santos, Sônia Cristina; Alves, Rômulo R. N.; Pereira-Filho, Gentil A. (Zootaxa, 2009)
The genus Phyllodytes, comprises twelve species (Frost 2008), and only the tadpoles of Phyllodytes auratus, P. melanomystax, P. gyrinaethes e P. edelmoi were described until now. The present work describes the tadpoles of P. brevirostris, using external morphological features and internal oral characteristics, and compares them to other tadpoles of species belonging to the genus.